2002
DOI: 10.1046/j.1439-0442.2002.jv408.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Distribution and Factors Associated with the Presence and the Potential for Malignancy of Cutaneous Neoplasms in 174 Dogs Admitted to a Clinic in Northern Greece

Abstract: One hundred and seventy-four dogs diagnosed with cutaneous neoplasms in the Animal Medical and Surgical Clinic, Faculty of Veterinary Medicine, Aristotle University of Thessaloniki, were studied. Thirty-one types of neoplasm were diagnosed, among which mast cell tumours (13.8%), hepatoid gland adenomas (9.8%), lipomas (5.7%) and histiocytomas (5.7%) were the most common. The prevalence of epithelial, mesenchymal, lymphohistiocytic and melanocytic tumours was 47.7, 40.8, 8.6 and 2.9%, respectively. Potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
56
3
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 16 publications
13
56
3
15
Order By: Relevance
“…In this study, the frequency of CLs was higher than HCTs. Studies on the prevalence of skin tumours in dogs show that the frequency of HCTs is greater than CLs, but in these cases, only histology was used as a diagnostic tool (Kaldrymidou et al 2002, Pakhrin et al 2007). The diagnosis of PCT, LHS and TVT using IHC (5.2%, 9/172, 3.5%, 6/172 and 4.1%, 7/172, respectively) was greater than the diagnoses using only histology (1.74%, 3/172, 1.17%, 2/172 and 0.06%, 1/172, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the frequency of CLs was higher than HCTs. Studies on the prevalence of skin tumours in dogs show that the frequency of HCTs is greater than CLs, but in these cases, only histology was used as a diagnostic tool (Kaldrymidou et al 2002, Pakhrin et al 2007). The diagnosis of PCT, LHS and TVT using IHC (5.2%, 9/172, 3.5%, 6/172 and 4.1%, 7/172, respectively) was greater than the diagnoses using only histology (1.74%, 3/172, 1.17%, 2/172 and 0.06%, 1/172, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Foi observado um maior número de neoplasmas cutâneos malignos do que benignos, resultado também identificado por Kaldrymidou et al (2002). Entretanto, difere de outros trabalhos de tumores cutâneos que apresentaram maior prevalência de benignos (Dobson et al 2002, Bellei et al 2006, Souza et al 2006, Pakhrin et al 2007.…”
Section: Discussionunclassified
“…Mastocitoma, lipoma, adenoma perianal, carcinoma de células escamosas, tricoblastoma e histiocitoma são alguns dos tumores cutâneos mais frequentes em cães (Rothwell 1987, Dobson et al 2002, Kaldrymidou et al 2002, Bellei et al 2006, Murphy 2006b, Souza et al 2006, Pakhrin et al 2007.…”
Section: Introductionunclassified
“…In this respect, Kaldrymidou et al (2002) observed that the odds of neoplasm presence were two times higher in pure bred dogs than in mongrels but did not differ between cross-breeds and mongrels.…”
Section: Discussionmentioning
confidence: 84%
“…Histopathologically, the recorded tumor was confirmed as fibroadenoma with a tendency of malignancy. In this respect, the odds of tumor malignancy linearly increased with increasing age by a factor of 1.1 per year (Kaldrymidou et al, 2002).…”
Section: Discussionmentioning
confidence: 91%